Pengaruh Model Edukasi Kesadaran Hak Asasi Manusia melalui Kampanye Digital terhadap Pemahaman tentang Kekerasan Berbasis Gender Online - Prayoga Bestari; Aim Abdulkarim; Rahmat Rahmat; Pitria Sopianingsih; Nisrina Nurul Insani; Diva Dwi Juliana (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2025)
This study examines the effect of a human rights awareness education model delivered through a digital campaign on university students’ understanding of Online Gender-Based Violence. The growing prevalence of online gender-based violence among students has become a critical concern due to its implications for digital security, privacy, and gender equality. Employing a quantitative approach with a correlational design, the study collected data through a questionnaire administered to 277 students at Universitas Pendidikan Indonesia. The digital campaign utilized an educational animated video titled Aku Ingin Rasa Aman as the primary intervention instrument. Descriptive analysis indicates a strong positive response from participants, with more than 90 percent of respondents agreeing or strongly agreeing that the video effectively enhanced their understanding of online gender-based violence. The findings demonstrate a positive and statistically significant influence of the human rights awareness education model implemented through digital campaigning on students’ comprehension of online gender-based violence. These results affirm the effectiveness of digital campaigns as an educational strategy for strengthening human rights awareness and promoting safer and more equitable digital spaces among university students.